Association between prealbumin, all‐cause mortality, and response to nutrition treatment in patients at nutrition risk: Secondary analysis of a randomized controlled trial. Issue 3 (27th January 2023) - Bretscher, Céline; Buergin, Michelle; Gurzeler, Gianna; Kägi‐Braun, Nina; Gressies, Carla; Tribolet, Pascal; Lobo, Dileep N.; Evans, David C.; Stanga, Zeno; Mueller, Beat; Schuetz, Philipp; ,
Abstract: Background: Because of the shorter half‐life as compared with albumin, serum prealbumin concentrations have been proposed to be useful nutrition biomarkers for the assessment of patients at nutrition risk. In a post hoc analysis of patients at nutrition risk from a randomized controlled nutrition trial, we tested the hypothesis that (1) prealbumin is associated with higher all‐cause 180‐day mortality rates and that (2) individualized nutrition support compared with usual‐care nutrition more effectively improves survival at 30 days in patients with low prealbumin levels compared with patients with normal prealbumin levels. Methods: We performed a prespecified cohort study in patients included in the pragmatic, Swiss, multicenter randomized controlled EFFORT trial comparing the effects of individualized nutrition support with usual care. We studied low prealbumin concentrations (<0.17 g/L) in a subgroup of 517 patients from one participating center. Results: A total of 306 (59.2%) patients (mean age 71.9 years, 53.6% men) had low admission prealbumin levels (<0.17 g/L). There was a significant association between low prealbumin levels and mortality at 180 days (115/306 [37.6%] vs 47/211 [22.3%], fully adjusted hazard ratio [HR]=1.59, 95% CI 1.11–2.28; P  = 0.011). Prealbumin levels significantly improved the prognostic value of the Nutritional Risk Screening total score regarding mortality prediction at short‐ and long‐term. The difference in mortality between patients receiving individualized nutrition support and usual‐care nutrition was similar for patients with low prealbumin levels compared with patients with normal prealbumin levels (HR=0.90 [95% CI=0.51–1.59] vs HR=0.88 [95% CI=0.35–2.23]) with no evidence for interaction ( P  = 0.823). Conclusion: Among medical inpatients at nutrition risk, low admission prealbumin levels correlated with different nutrition markers and higher mortality risk, but patients with low or high prealbumin levels had a similar benefit from nutrition support. Further studies should identify nutrition markers that help further personalize nutrition interventions.